Autoimmunity, cancer and COVID-19 abnormally activate wound healing pathways: critical role of inflammation - Gál, Peter; Brábek, Jan; Holub, Michal; Jakubek, Milan; Šedo, Aleksi; Lacina, Lukáš; Strnadová, Karolína; Dubový, Petr; Hornychová, Helena; Ryška, Aleš; Smetana, Karel (Histochemistry and cell biology, 2022)
Recent evidence indicates that targeting IL-6 provides broad therapeutic approaches to several diseases. In patients with cancer, autoimmune diseases, severe respiratory infections [e.g. coronavirus disease 2019 (COVID-19)] and wound healing, IL-6 plays a critical role in modulating the systemic and local microenvironment. Elevated serum levels of IL-6 interfere with the systemic immune response and are associated with disease progression and prognosis. As already noted, monoclonal antibodies blocking either IL-6 or binding of IL-6 to receptors have been used/tested successfully in the treatment of rheumatoid arthritis, many cancer types, and COVID-19. Therefore, in the present review, we compare the impact of IL-6 and anti-IL-6 therapy to demonstrate common (pathological) features of the studied diseases such as formation of granulation tissue with the presence of myofibroblasts and deposition of new extracellular matrix. We also discuss abnormal activation of other wound-healing-related pathways that have been implicated in autoimmune disorders, cancer or COVID-19.
Keywords: autoimunitní nemoci; hojení ran; COVID-19; lidé; Granulation tissue; Wound Healing; Cancer stroma; Rheumatoid arthritis; Tumor Microenvironment; Wound healing; Humans; Myofibroblast; Autoimmune Diseases; Inflammation; IL-6; autoimunita; zánět; nádorové mikroprostředí; Peripheral nerve injury; nádory; SARS-CoV-2; Autoimmunity; Neoplasms